Tetralogy of Fallot in Spain: a nationwide registry-based mortality study across 36 years - Laura Llamosas-Falcón; Eva Bermejo-Sánchez; Germán Sánchez-Díaz; Ana Villaverde-Hueso; Manuel Posada de la Paz; Verónica Alonso-Ferreira (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Tetralogy of Fallot (TOF) is the most frequent cyanotic congenital heart defect. TOF mortality has fallen remarkably in recent years due to therapeutic advances. Accordingly, the aim of this study was to assess temporal and spatial variability in TOF-related mortality in Spain across the period 1981–2016, using data drawn from the nationwide population-based registry. Methods Annual deaths due to TOF were sourced from the Spanish National Institute of Statistics database by reference to International Classification of Diseases (ICD), 9th and 10th Revision codes, namely, ICD-9 code 745.2 (period 1981–1998) and ICD-10 code Q21.3 (period 1999–2016). Age-specific and age-adjusted mortality rates were calculated, as were standardised mortality ratios (SMRs) by province, district and municipality for the period 1999–2016. Results A total of 1035 deaths were attributed to TOF (57.78% of them were men and 42.22% were women). The age-adjusted mortality rate ranged from 0.75 per 1,000,000 inhabitants (95% confidence interval [CI]: 0–1.36) in 1981 to 0.03 per 1,000,000 (95% CI: 0.01–0.06) in 2016 for both sexes. In 2011, there was a change in the mortality trend, with a significant decrease of 49.22% per year (p < 0.001). In terms of geographical analysis, some areas with a significantly higher risk of TOF mortality were identified in the south of Spain, though no specific spatial pattern was in evidence. Conclusion The decrease in TOF mortality may be related to improvements in diagnostic and treatment techniques. More studies are needed to analyse regions with a higher mortality risk, in order to improve medical planning and resource allocation, and identify risk factors and preventive measures.